E-111 Analysis of intracerebral hemorrhage in n established mouse model. (23rd July 2022) - Pendleton, N
Abstract : Background: Kontos' elucidated the theory that iron-mediated free radical production and subsequent oxidative damage was responsible for on-going cerebral degeneration within the infarct following ischemic stroke. The production of free radicals is likely tied to the generation of superoxide following reperfusion of the ischemic brain. Free radical production happens relatively soon after reperfusion but the time to oxidative damage of surrounding tissue is still unknown. It is well-established that ischemic stroke results in loss of autoregulation to cerebral tissues. Ischemic strokes have the potential to transform into hemorrhagic lesions. There is less known about the timeline of oxidative damage to the surrounding tissues after the point of transformative hemorrhage. We characterized the initial intracerebral hemorrhage (ICH) event with an in-house mouse model and tracked oxidative biomarkers in the hemorrhagic core, peri-hematoma zone, contralateral brain tissue and in sham mice using Fourier transform infrared (FTIR) imaging and X-ray fluorescence imaging (XFI) at consecutive time points post-ICH. We strive to provide a clear picture of the natural history of events that occur following the hemorrhagic transformation of ischemic stroke. We also strive to identify intervenable chemical processes and biomolecular targets for subsequent treatments aimed at preventing collateral damage to healthy brain tissue. Methods: Mice are anesthetized using isoflurane, followed by preparation, and shaving of the surgical site. Mice will be transferred to a stereotactic frame for controlled, automated injection. A midline incision in the scalp to identify bregma. From bregma, we will use the stereotactic frame to navigate over the right cortex, which will be marked for burr hole drilling. Collagenase will be injected following our already-established ICH protocols. Initiation of collagenase injection will be the 0-hour time point. We wake the mice and monitor them until they reach their randomly-assigned time point. We prepare culled brains for sectioning after cryofreezing. Analysis and Interpretation: Metabolic maps are in the process of being obtained for each tissue, as shown in Figure 1 . We will compare the tissue distribution and concentration of metabolites over time. The isolated metabolites can be directly linked to tissue health and viability. We will gain insights into the evolution of the oxidation, and therefore damage to the hematoma, peri-hematoma zone and surrounding healthy brain tissue. Disclosures: N. Pendleton: None.